(untitled) (Journal of Comparative & International Higher Education, 2021)
Although global higher education partnerships can promote greater intercultural understanding, establish unique environments for student and faculty development, and generate opportunities for innovative and entrepreneurial ventures, they can be beset with problems that negate their potential effectiveness. This paper proposes that open systems theory offers a constructive lens for reimagining global higher education partnerships so that they not only benefit internal stakeholders, but also society. It begins with the basic concepts associated with systems theory, with particular attention to the differences between rational and natural systems, as well as open and closed systems. To project how open systems theory might encourage global partnerships to embrace institutional outreach with the environment, the relationship of open systems theory with community engagement is then explored. Finally, the paper shows how boundaries can be either reinforced or traversed through deliberate buffering, bridging, and boundary spanning strategies.